2013
DOI: 10.1111/ddi.12105
|View full text |Cite
|
Sign up to set email alerts
|

Multicolony tracking reveals potential threats to little auks wintering in the North Atlantic from marine pollution and shrinking sea ice cover

Abstract: Aim Extensive development of human activities in combination with ocean warming is rapidly modifying marine habitats in the Arctic and North Atlantic regions. To understand the potential impacts on marine biodiversity, there is an urgent need to determine distributions and habitat preferences of potentially vulnerable species and to identify sensitive hotspots that might require particular protection. Our aims were to track one of the most abundant seabirds of the world, the little auk (Alle alle), to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 33 publications
2
68
1
Order By: Relevance
“…Some winter recoveries of little auks ringed in the breeding colonies in western Spitsbergen and northwestern Greenland indicate that waters off southwestern Greenland are an important wintering area for both of these populations (Isaksen and Bakken 1996). Also, a recent study on birds equipped with geolocator tags showed substantial overlap of the wintering areas among birds from breeding grounds on east and west Greenland and the Svalbard archipelago including Bear Island (Fort et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some winter recoveries of little auks ringed in the breeding colonies in western Spitsbergen and northwestern Greenland indicate that waters off southwestern Greenland are an important wintering area for both of these populations (Isaksen and Bakken 1996). Also, a recent study on birds equipped with geolocator tags showed substantial overlap of the wintering areas among birds from breeding grounds on east and west Greenland and the Svalbard archipelago including Bear Island (Fort et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Labrador Sea is important to marine birds yearround supporting breeding seabird colonies during summer and providing important staging, migration, and wintering habitat for seabirds from colonies in both the northern and southern hemisphere (Brown, 1986;Huettmann and Diamond, 2000;Bakken and Mehlum, 2005). Recent tracking information shows movements of North Atlantic breeding seabirds to staging and wintering areas in eastern Canadian and Greenlandic waters that include the Labrador Sea, highlighting the international importance of these waters (Frederiksen et al, 2012(Frederiksen et al, , 2016Mosbech et al, 2012;Fort et al, 2013;Jessopp et al, 2013;Linnebjerg et al, 2013;McFarlane Tranquilla et al, 2013). However, explicit local-scale spatial information on seabird distribution in the Labrador Sea has been limited by patchy marine survey coverage (Fifield et al, 2009), mostly due to logistical difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean warming has been linked to a poleward redistribution of cold-water zooplankton species (Hays et al 2005, Beaugrand et al 2009), and could lead to major shifts in the location and strength of the principal Southern Ocean fronts (Bargagli 2005). These perturbations alter food-web structure at high latitudes with consequences for zooplanktivorous seabirds (Guinet et al 1998, Fort et al 2013, including alterations to both the phenology and direction of their migration (Quillfeldt et al 2010, Thompson et al 2012.…”
Section: Introductionmentioning
confidence: 99%